Parallel implementation of vertex component analysis for hyperspectral endmember extraction - Alves, José M. Rodriguez (2014)
International Conference with Peer Review 2012 IEEE International Conference in Geoscience and Remote Sensing Symposium (IGARSS), 22-27 July 2012, Munich, Germany